Retrograde mastoidectomy technique - retrospective analysis of results - Mourão, Márcia (2024)
Objective: Analysis of the results of mastoidectomy using the retrograde technique for removal of cholesteatomas in adults. Methods: Retrospective analysis of cases of mastoidectomy via retrograde technique performed at Centro Hospitalar Tondela-Viseu between January 2018 and December 2021 with collection of demographic data, type of surgery, reconstruction of the posterosuperior wall of the canal, type of tympanoplasty, recurrence, follow-up time and audiometric results. Results: 45 ears were included in the study, 73.3% of which corresponded to primary surgery. Reconstruction of the posterosuperior wall of the canal was performed in 37.8% and ossiculoplasty was done in 73.3%. The air-bone gap gain, in patients who underwent wall reconstruction was 9.66dB (vs. 1.91 dB without reconstruction). During follow-up, recurrence occurred in 13.3% of cases. Conclusions: In our series, this technique proved to be safe and effective in cholesteatoma excision. Reconstruction of the EAC wall allowed better audiometric results.